Patterns of democracy : government forms and performance in thirty-six countries - Lijphart, Arend (Yale University Press, 2012)
In this updated and expanded edition of his classic text, Arend Lijphart offers a broader and deeper analysis of worldwide democratic institutions than ever before. Examining thirty-six democracies during the period from 1945 to 2010, Lijphart arrives at important--and unexpected--conclusions about what type of democracy works best.--